2015
DOI: 10.1186/s12981-015-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Rates and risk factors associated with the progression of HIV to AIDS among HIV patients from Zhejiang, China between 2008 and 2012

Abstract: ObjectivesThe objective of this study was to determine the rate of acquired immune deficiency syndrome (AIDS) in Zhejiang province and to identify specific factors associated with progression of this disease.MethodsThis study utilized a retrospective cohort to identify the specific factors involved in the progression of human immunodeficiency virus (HIV) to AIDS. We collected data of patients existing in care between 2008 and 2012 from the national surveillance system databases. We performed our analyses using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Findings of the present study showed a strong relationship between disease stage, sexually transmitted disease (STD), CD4+ T-cell count, HBV coinfection, and AIDS with the survival time of HIV patients. In developed countries, several factors were reported including tuberculosis and HBV coinfection, intravenous drug abuse, CD4+ cell count lower than 500 cells/mm 3 , and black or brown skin as predictors for AIDS progression [19]. Based on data from the routine reporting system in Iran, up to the middle of 2009, 20,130 HIV-positive cases were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of the present study showed a strong relationship between disease stage, sexually transmitted disease (STD), CD4+ T-cell count, HBV coinfection, and AIDS with the survival time of HIV patients. In developed countries, several factors were reported including tuberculosis and HBV coinfection, intravenous drug abuse, CD4+ cell count lower than 500 cells/mm 3 , and black or brown skin as predictors for AIDS progression [19]. Based on data from the routine reporting system in Iran, up to the middle of 2009, 20,130 HIV-positive cases were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al assessed rates and risk factors associated with the progression of HIV to AIDS among HIV-positive patients. They demonstrated that factors, including age, implementing HAART treatment, and early diagnosis and treatment can efficiently increase the time between progression of HIV to its' final and most severe stage, AIDS [18]. We found that older patients were more prone to earlier progression to AIDS.…”
Section: Discussionmentioning
confidence: 62%
“…Yang et al [17] suggested that in comparison with HIV-infected individuals infected through contaminated blood transmission, HIV-infected individuals infected through homosexual transmission had significantly lower mortality risk, while HIV-infected individuals whose transmission was through heterosexual transmission exhibited higher mortality risk. Conversely, Chen et al [18] and Yan et al [19] found that compared with those infected by blood transmission, HIV-infected individuals infected by homosexual transmission exhibited a significantly higher hazard ratio for progression to AIDS. In their opinions, the high rate of progressing to AIDS among homosexual patients may be due to less social and familial support, stigma, psychological characteristics and so on.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, Chen et al . [18] and Yan et al . [19] found that compared with those infected by blood transmission, HIV-infected individuals infected by homosexual transmission exhibited a significantly higher hazard ratio for progression to AIDS.…”
Section: Discussionmentioning
confidence: 99%